Pertumbuhan dan Hasil Beberapa Genotipe Sorgum (Sorghum bicolor (L.) Moench) pada Berbagai Jarak Tanam - A’yun, Qurrata; Anwar, Aswaldi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
Sorghum is one of the alternative food crop that can be developed as an effort for food diversify.One of the efforts that can be done for the development of sorghum is by using several genotypes and planting distance. This study aims to determine the growth and yield of several genotypes of sorghum at various planting distances. The research was carried out at the Experimental Garden of the Faculty of Agriculture, Andalas University, Padang, from January to May 2022. This study used an experimental method with a Randomized Block Design (RBD) consising of 2 factors. The first factor was the planting distance of the plants which consist of three levels, namely 70 cm x 10 cm, 70 cm x 20 cm and 70 cm x 30 cm. The second factor was the genotype which consist of three genotypes, namely genotype 76-1, genotype 103-1 and Bioguma5Agritan genotype. The data were analyzed by F test and if the calculated F value is greater than F table 5%, then it is continued with the Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The results showed that the genotypes produced the same growth and yield. Planting distance of 70 cm x 30 cm had the best effect on stem diameter, panicle lenght, panicle fresh weight, dry seed weight per panicle and 1000 seed weight.